2013
DOI: 10.1007/s00436-013-3300-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for bacteria-independent hatching of Trichuris muris eggs

Abstract: Hatching of infective larvae from embryonated eggs in the intestine is an essential first step in Trichuris infections. There are three isolates of the murine parasitic nematode Trichuris muris: E, E-J (the E isolate maintained in Japan), and S. Incubation of T. muris embryonated eggs with the intestinal bacteria Escherichia coli and Staphylococcus aureus induced in vitro hatching of the eggs, but Enterococcus faecalis failed to induce hatching. Bacteria-induced in vitro hatching of embryonated eggs occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The experiments showed that E. coli and S. aureus could induce the hatching of E and E-J T. muris eggs under in vitro conditions while E. faecalis could not stimulate the same. Under the same conditions the S isolates were found to be unresponsive to bacterial stimulation [31]. It was also experimentally demonstrated that the egg hatching was suppressed (in E and E-J isolates) when the experiments were carried out in presence of an antibiotic (kanamycin) or when the bacteria used in the experiments were previously incubated at 4°C or fixed with formaldehyde [31].…”
Section: Providing Aid To Life-cycle Associated Phenomena Of the Helmmentioning
confidence: 92%
See 4 more Smart Citations
“…The experiments showed that E. coli and S. aureus could induce the hatching of E and E-J T. muris eggs under in vitro conditions while E. faecalis could not stimulate the same. Under the same conditions the S isolates were found to be unresponsive to bacterial stimulation [31]. It was also experimentally demonstrated that the egg hatching was suppressed (in E and E-J isolates) when the experiments were carried out in presence of an antibiotic (kanamycin) or when the bacteria used in the experiments were previously incubated at 4°C or fixed with formaldehyde [31].…”
Section: Providing Aid To Life-cycle Associated Phenomena Of the Helmmentioning
confidence: 92%
“…Under the same conditions the S isolates were found to be unresponsive to bacterial stimulation [31]. It was also experimentally demonstrated that the egg hatching was suppressed (in E and E-J isolates) when the experiments were carried out in presence of an antibiotic (kanamycin) or when the bacteria used in the experiments were previously incubated at 4°C or fixed with formaldehyde [31]. However, differences in infectivity of E-J and S isolates were not observed [31].…”
Section: Providing Aid To Life-cycle Associated Phenomena Of the Helmmentioning
confidence: 95%
See 3 more Smart Citations